Gut microbiota and mechanism of liver cancer - CHEN Congyan, WANG Junqing, CHEN Yongjun (Waike lilun yu shijian, 2022)
Liver cancer incidence in China is higher with new cancer cases accounted for 46.7% of global prevalence and death cases 47.1%. Hepatic virus, aflatoxin and alcohol drinking are the risk factors associated with the mechanism of liver cancer. Study on gut microbiota in recent years was ongoing deeply, indicating gut microbiota associated with the development of liver cancer. Liver cancer with gut microbiota was studied in this paper for microbiota displacement, intestinal endotoxemia, and changes in bacterial metabolite, including the new ideas in treatment of liver cancer via gut microbiota from probiotics, fecal microbiota transplantation, antibiotics and Toll-like receptor 4 antagonist pathways.